2022
DOI: 10.21163/gt_2022.172.03
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Particulate Matter Less Than 10 Microns Volume Through Various Formats of Spatial Interpolation Methods

Abstract: The problem on air pollution, especially the problem on smoke caused by accumulation of smoke and dust in the air, is considered as one of important problems in Thailand and this problem is currently more serious increasingly. This study aims to study on relationship between Particulate Matter Less Than 10 Microns (PM10) volume in northern area and physical factors of the area as well as estimate PM10 through various formats of Spatial Interpolation Methods and study on appropriateness of each method. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the past measuring particulate matter in the atmosphere could be done by measuring tools and sensors only (Pollution Control Department, 2023), later Remote Sensing Technology was used to measure the quantity of particulate matter by using data from natural resources and environment observation satellites. After researching documents and relevant research found that data from satellites has been used to estimate particulate matter in the atmosphere such as research on "Spatiotemporal Patterns of PM10 Concentrations over China during 2005-2016: A Satellite-based Estimation using the Random Forests Approach" by Chen et al, (2018), research on Patterns of Relationship between PM10 from Air Monitoring Quality Station and AOT Data from MODIS Sensor Onboard of Terra Satellite" by Suriya et al, (2021), research on "Estimation of Ground PM2.5 Concentrations in Pakistan Using Convolutional Neural Network and Multi-Pollutant Satellite Images" by Ahmed et al, (2022), research on "The Human Health Risk Assessment of Particulate Air Pollution (PM2.5 and PM10) in Romania" by Bodor et al, (2022), and research on " Estimation of Particulate Matter Less Than 10 Microns Volume through Various Formats of Spatial Interpolation Methods" by Itsarawisut & Laosuwan (2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the past measuring particulate matter in the atmosphere could be done by measuring tools and sensors only (Pollution Control Department, 2023), later Remote Sensing Technology was used to measure the quantity of particulate matter by using data from natural resources and environment observation satellites. After researching documents and relevant research found that data from satellites has been used to estimate particulate matter in the atmosphere such as research on "Spatiotemporal Patterns of PM10 Concentrations over China during 2005-2016: A Satellite-based Estimation using the Random Forests Approach" by Chen et al, (2018), research on Patterns of Relationship between PM10 from Air Monitoring Quality Station and AOT Data from MODIS Sensor Onboard of Terra Satellite" by Suriya et al, (2021), research on "Estimation of Ground PM2.5 Concentrations in Pakistan Using Convolutional Neural Network and Multi-Pollutant Satellite Images" by Ahmed et al, (2022), research on "The Human Health Risk Assessment of Particulate Air Pollution (PM2.5 and PM10) in Romania" by Bodor et al, (2022), and research on " Estimation of Particulate Matter Less Than 10 Microns Volume through Various Formats of Spatial Interpolation Methods" by Itsarawisut & Laosuwan (2022).…”
Section: Introductionmentioning
confidence: 99%